CORRELATION AMONG READING INTEREST, READING SELF-EFFICACY, AND READING COMPETENCY IN THE JUNIOR HIGH SCHOOL - Handayani, Made Ari Juli; Tantra, Dewa Komang; Agustini, Dewa Ayu Eka (Universitas Pendidikan Ganesha, 2020)
The current research objectives were to describe and to relate the students’ reading interest, reading self-efficacy to their reading competency in the Sekolah Menengah Pertama Negeri 8 Singaraja. The subject were the students in the eight-grade students. This research was designed a quantitative research. The data were gathered using reading interest scale, reading self-efficacy scale, and objective reading competency test. The obtained data were analyzed in two phases, namely: descriptively, that is the description consisted of central tendency and inferentially, that is the data were analyzed using pair-wise correlation and multiple correlation technique. The findings show that: 1) the students’ reading interest, reading self-efficacy, and reading competency on high-order-items are at the moderate levels;2) the relations pair-wisely between the students’ reading interest and reading self-efficacy, students reading interest and reading competency, the students’ reading self-efficacy and reading competency on high-order-items are positively and significantly correlated; and 3) the simultaneous or multiple relationships of the reading interest and reading self-efficacy to the students’ reading competency is proven to be significant.